KOMODIFIKASI PROGRAM BERITA LIPUTAN 6 PAGI SCTV - Dina Andriana; Widarti Widarti; I Ketut Martana (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Commodification was carried out by the editor as an effort to maintain the existence of an event program, this was also done by the editor of Liputan 6 Pagi, SCTV. The research method used is a case study. Data collection methods used are interviews, and literature studies with qualitative analysis using the theory of Political Media Politics by Vincent Mosco. This study also revealed that there is a news commodification on the news that is broadcast. Commodification of audiences is done in packaging news by paying attention to the interests of the audience. The types of workers who intersect with media workers, but media workers get comfort and job satisfaction, which may be unwittingly capable and maximally utilized by SCTV. Keywords: Commodification, News Program, Editor, Liputan 6 Pagi, SCTV.